Effect of a nitric oxide donor on maternal hemodynamics in fetal growth restriction. (10th April 2018) - Tiralongo, G. M.; Pisani, I.; Vasapollo, B.; Khalil, A.; Thilaganathan, B.; Valensise, H.
ABSTRACT: Objective: To evaluate the effect on maternal cardiovascular parameters of treatment with a nitric oxide (NO) donor and plasma volume expansion in pregnancies complicated by fetal growth restriction (FGR). Methods: Twenty‐six pregnant women with a diagnosis of FGR were treated with transdermal patches of a NO donor and plasma volume expansion by co‐administration of oral fluids. We compared the treated group to a historical control group of untreated FGR patients. Hemodynamic indices were obtained using the UltraSonic Cardiac Output Monitor system. Results: At diagnosis, the two groups were similar in terms of maternal and hemodynamic characteristics. In the treated group, we found a significant increase in maternal cardiac output and stroke volume and a decrease in systemic vascular resistance after 2 weeks of therapy. No significant differences were found 2 weeks after diagnosis in the untreated group. The treated group delivered infants with higher birth‐weight centile than did the untreated control group. Conclusions: The combined therapeutic approach of NO donor administration and plasma volume expansion in FGR apparently improves significantly maternal hemodynamic indices. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.